Elaboración de las principales recetas tradicionales ibarreñas a base de carne de borrego - Villacreses Torres, Alexander Santiago (2021)
Gastronomy is the science that studies man and his environment, related to the way of eating, where he goes from surviving to acquiring certain knowledge about his diet, where it not only consists of ingesting breath to satisfy hunger, but also sew on acquire knowledge about their identity, culture and gastronomy, where these aspects are fundamental for a development in man and how he feeds. The present research aims to diversify the use of lamb meat according to the main traditional recipes of the Canton Ibarra, in order to enhance the consumption of this type of meat. For this purpose, the following specific objectives were raised: determine theoretical foundations through the bibliographic compilation on lamb meat and traditional dishes in the Canton Ibarra and a demand study to know if consumers would be willing to taste traditional preparations based on of lamb meat. The methodology was based on bibliographic research and field research through a survey aimed at consumers of sheep meat to find out their perceptions and acceptance of traditional dishes based on lamb meat. In addition, 4 interviews have been carried out aimed at gastronomy professionals. With the results obtained, a cookbook has been prepared with new preparations based on lamb meat, focusing on the most important traditional recipes of the Canton Ibarra. Through this research and contribution, an innovative product can be offered, highlighting the preparations that identify it as a canton with a gastronomy known, varied and specific for its traditional flavor.